EVALUASI VIGOR DAYA SIMPAN BENIH PADA BERBAGAI GENOTIPE CABAI (CAPSICUM ANNUUM L.) DENGAN METODE PENGUSANGAN CEPAT - Ekowahyuni, Luluk Prihastuti; Sutjahjo, Surjono Hadi; Sujiprihati, Sriani; Suhartanto, Mohamad Rahmad; Syukur, Muhamad (E-Journal Widya Kesehatan dan Lingkungan, 2014)
Abstrak:       Percobaan ini bertujuan mengevaluasi metode pengusangan cepat methanol 20% selama 0, 2, 4, 6 dan 8 jam pada benih cabai hibrida, non hibrida, lokal, introduksi, rawit dan besar yang diproduksi pada tahun 2009 dan 2010. Jumlah genotipe benih non hibrida 4 (2009) dan 4 (2010). Jumlah genotipe benih hibrida 10 (2009) dan 8 (2010). Analisis data dilakukan dengan analisis sudut kemiringan garis regressi yang merupakan sudut  perbandingan ordinat dan axis. Rekapitulasi hasil evaluasi vigor daya simpan benih cabai menunjukkan bahwa tidak ada perbedaan antara benih produksi tahun 2009 dan 2010, dan benih cabai hibrida dan  non hibrida, serta benih cabai lokal dan introduksi. Perbedaan terdapat pada benih cabai rawit dan besar dan laju penurunannya cabai besar lebih cepat dibandingkan benih cabai rawit.  Hal ini terjadi juga pada tolok ukur daya hantar listrik yang merupakan tolok ukur terbaik untuk vigor daya simpan benih. Hal ini menunjukkan besarnya pengaruh lingkungan terhadap vigor daya simpan benih cabai. Kata kunci: deteriorasi alami, laju kemiringan vigor daya simpan benih cabai. Abstract    The experiment was designed to evaluate the accelerated aging method with 20% methanol for 0, 2, 4, 6 and 8 hours which is the first stage of the experimental results at several pepper seed genotypes including hybrid seeds, non hybrid, local, introduction, pepper and great pepper produced in 2009 and 2010. The seeds used are non-hybrid seed as much as 4 genotype seed production in 2009 and 4 genotype seed production in 2010. Hybrid seeds used were 10 genotypes of production in 2009 and 8 genotypes of production in 2010. Data analysis done is the analysis of the slope angle of regression line slope which is resulting from the comparison of the ordinate and the axis. Recapitulation of the pepper seeds vigor storage evaluation results showed that the seed production in 2009 and 2010 there was no difference between the hybrid and non-hybrid pepper seeds and the local and introduction pepper seeds, but there are consistent differences between great chili and chili pepper seeds, the rate of decline of the great chili is greater than the chili pepper. This shows the magnitude of environmental influences on seed pepper seeds vigor storage. Exclusively in electrical conductivity benchmark, which is one of the pepper seeds vigor storage best benchmark shows that the rate of decline in seed vigor between the hybrid and non hybrid seeds and the local and introduction pepper seeds.. Key words: natural deterioration, the rate of decline seed pepper vigor test in relation  to storability